Finance : The basics - Banks, Erik. (London : Routledge, 2023)
"Now in its fourth edition, Finance: The Basics is a clear and practical introduction to the world of finance. It thoroughly explains essential financial statements, tools and concepts; fundamental financial instruments and transactions; and global financial participants, markets and systems. This fully revised edition captures the most important aspects of a changing financial landscape, including: -A new chapter dedicated to the emerging world of digital currencies, with a review of digital finance and a detailed discussion of regulated and unregulated digital currencies (including cryptocurrencies). - New sections dealing with a range of social issues that directly impact on finance, including sustainability, environmental, social and governance (ESG) and socially responsible investing (SRI) imperatives, microfinance, and impact investing. - Twelve updated real-world case studies ("Finance in action" studies) and nine new case studies focused on annuities, sustainability, green financings, microfinance, digital currencies, financial technology/decentralized finance, ESG and SRI investing, quantitative easing and tightening, and the financial emergence of China. - A concise and comprehensive glossary containing key terms discussed in the book. - Supplemental digital resources, including PowerPoints for instructors and a test bank of questions for students. Each chapter is accompanied by an overview and summary, illustrations and tables, real-life case studies, and recommended readings. Finance: The Basics is essential reading for anyone interested in the fascinating world of finance"--
Includes bibliographical references and index.
Keywords: Finance